Design of a new cost-efficient automation system for gas leak detection in industrial buildings - Ayaz, Murat; Yüksel, Hüseyin (Energy and buildings, 2019)
•A new cost-efficient gas leak detection system has been designed for industrial buildings.•Centralized gas leak measurement from a single point is proposed instead of distributed measurement.•A cost saving of 75% has been achieved compared to conventional systems.•The proposed system has a similar performance to conventional systems. In industrial facilities, dangerous gas leaks may occur that are potentially harmful to human health and the working environment. Conventional gas measurement and control systems are commonly used to ensure a safe working environment. However, these systems have very high installation costs due to expensive components and further, this cost increases depending on the size of the site, the number of measurement points and the gas types. In this study, the design and implementation of a new low-cost gas leak detection system that has a simple control structure with a single sensor set have been carried out. In the proposed system, the measurement points in the area, where gas leaks are being detected, are combined with pipelines in a single measurement center. The air samples are taken from the measurement points through the pipes to the measuring center with a certain sequence starting from the first point to the last and are measured by a single sensor unit consisting of different gas sensors. The one cycle time required to measure all points is determined based on the length and diameter of the pipes, the number of measuring points and the specifications of the gases. The proposed system has been designed to measure H2S, CO, CH4 and O2 gases up to five measurement points within a 70-second cycle. Data accusation, control and monitoring of the system have been carried out with a programmable logic controller and Supervisory Control and Data Acquisition system. The proposed and conventional systems have been installed in an industrial storage building to obtain experimental performance data. Compared to the conventional system, the proposed system detects gas leaks with a delay of about three to nine seconds depending on the distance from the point at which the gas leak occurred to the measurement center. Besides gas leak detection, the gas leak value is measured with a difference between two and five ppm. As a result, the proposed system provides a similar measurement performance at a cost of approximately 75% less than conventional systems. In addition, since the sensor unit is located outside of the building, fires or explosions caused by the ignition source have been eliminated, which thus contributes to the reduction of the security risk.